Book Review: Online, Blended, and Distance Education: Building Successful Programs in Schools - Roycroft, Anne (Online Learning, 2015)
Editors Tom Clark and Michael Barbour assemble an array of research and case studies from some of today’s leading scholars in digital learning in this user-friendly compilation. With over 30 years of experience in online learning research between them, Clark and Barbour’s wisdom is evident in their choices of contributors and themes. The book provides a greatly needed overview of research in online teaching and learning, which also shows that there is ample opportunity for investigation and innovation. Chapters on instructional design, technology infrastructure, and equitable access provide useful summaries for program planning, while the variety of case studies will no doubt trigger expanded investigation and future study.